Careful consideration when responding to new data: dolutegravir and pregnancy - C. Foster; S. Fidler; E.G.H. Lyall; G.P.T. Taylor (Elsevier, 2018)
This case highlights the current complexities of managing women in the early stages of pregnancy presenting on dolutegravir-based regimens. When responding to new data, there is an important decision to be made, between the potential, uncertain risk of teratogenicity against the potential increased risk of in utero vertical transmission of HIV-1.